2003
DOI: 10.1029/2002ja009765
|View full text |Cite
|
Sign up to set email alerts
|

Climatology and latitudinal gradients of quiet time thermospheric neutral winds over Millstone Hill from Fabry‐Perot interferometer measurements

Abstract: [1] Midlatitude nighttime thermospheric neutral winds are strongly dependent on season, solar activity, and latitude. We use an extensive database of wind measurements made during 1989-2001 by the Millstone Hill Fabry-Perot interferometer to study the detailed climatology of quiet time neutral winds near an altitude of 250 km. To facilitate the analysis of these data, we develop a local time, day-of-year, solar flux, and latitudedependent empirical model, with the latitude dependence obtained by considering no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
95
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(99 citation statements)
references
References 21 publications
3
95
1
Order By: Relevance
“…Therefore the stronger zonal wind can give rise to larger |R| for lower solar activity ( Figure 6). Zonal wind climatology over Millstone Hill has been published based on FPI measurements for a full solar cycle in 1989-2001 [15]. It was indicated that the eastward wind reach maximum before but close to midnight; the eastward wind in the evening is highest in winter; the eastward wind speed tends to be enhanced toward low solar activity, in particular, in winter.…”
Section: Zonal Wind Climatologymentioning
confidence: 99%
“…Therefore the stronger zonal wind can give rise to larger |R| for lower solar activity ( Figure 6). Zonal wind climatology over Millstone Hill has been published based on FPI measurements for a full solar cycle in 1989-2001 [15]. It was indicated that the eastward wind reach maximum before but close to midnight; the eastward wind in the evening is highest in winter; the eastward wind speed tends to be enhanced toward low solar activity, in particular, in winter.…”
Section: Zonal Wind Climatologymentioning
confidence: 99%
“…The meridional winds at mid-latitude are consistent with the solar EUV forcing and the consequent latitudinal pressure gradients, namely poleward by day and equatorward at night (Hagan, 1993;Kawamura et al, 2000). At higher mid-latitudes, the meridional winds can be influenced by the aurorally driven high-latitude circulation cell even under quiet conditions (Hagan, 1993;Emmert et al, 2003).…”
Section: Introductionmentioning
confidence: 71%
“…Similarly, the strong meridional gradients have been reported by Salah et al (1987) very significant latitudinal gradients for meridional winds at all seasons, especially during equinox periods at solar minimum. The strong positive latitudinal gradients for VEWs and meridional winds at southern higher mid-latitudes suggest an influence by the high-latitude magnetospheric convection (Hagan, 1993; Emmert et al, 2003). Strong gradients also appear at higher mid-latitudes during summer solstice periods near noon.…”
Section: The Latitudinal Gradient Of Vewsmentioning
confidence: 98%
See 2 more Smart Citations